Evaluasi Kriteria Kesesuaian Lahan Kopi Arabika Gayo 2 di Dataran Tinggi Gayo - Reza Salima; Abubakar Karim; Sugianto Sugianto (Jurnal Manajemen Sumberdaya Lahan, 2012)
Evaluation Criteria of Land Suitability to Arabica Gayo 2 coffee in the Gayo HighlandsAbstract. Nowadays, coffee development policy is directed at production increasing and physical quality of coffee bean. To reach the best production and physical quality of Arabica coffee bean, the cultivation should be conducted on suitable land and follow the requirement for each variety of Arabica coffee. This research is conducted to evaluate the criteria of the land suitability for Arabica Gayo 2 coffee, and to define the land characteristic based on climate and soil that can affect the physical quality of Arabica Gayo 2 coffee bean. This research is treated by using survey method with descriptive analysis and soil sample analysis in the laboratory that taken from each observation site. The observation sites are examined based on altitude and slope of the land. Soil samples were analyzed about the physical and chemical characteristic of the soil. Characteristic and quality of the land from each observation sites were compared with criteria of Arabica coffee land suitability. Meanwhile, to observe the relationship between land characteristic and Arabica Gayo 2 is conducted by multiple linear correlation analysis. The results show that all of the observation sites have actual land suitability class S3 (represented marginally) and S2 (represented enough) with factors of land altitude limiting, land slope, and soil chemical properties. Potential land suitability class of S2 is represented enough with factors of land altitude limiting, land slope, rooting media (effective depth), soil texture, stone surface, and nutrient availability. Potential land suitability class of S3 is represented marginally with land limiting altitude factor. The highest of production average is obtained at Potential land suitability class of S2 with the highest production at land altitude 1400 meters above sea level and slope 40%.Abstrak. Saat ini kebijaksanaan pengembangan kopi diarahkan pada peningkatan produksi dan  kualitas fisik biji kopi. Untuk mendapatkan produksi dan kualitas fisik biji yang baik maka penanaman kopi Arabika harus dilakukan pada lahan-lahan yang sesuai dan memenuhi persyaratan bagi masing-masing varietas kopi Arabika. Penelitian ini bertujuan untuk mengevaluasi kriteria kesesuaian lahan kopi Arabika Gayo 2 serta menetapkan karakteristik lahan berdasarkan iklim dan tanah yang menentukan kualitas fisik biji kopi Arabika Gayo 2. Penelitian dilakukan dengan menggunakan metode survei dengan analisis deskriptif serta analisis contoh tanah di laboratorium yang diambil dari masing-masing tapak pengamatan. Tapak pengamatan yang diperiksa dibuat berdasarkan ketinggian tempat dan kemiringan lereng. Sampel tanah yang dianalisis adalah fisik dan kimia tanahnya. Karakteristik dan kualitas lahan dari masing-masing tapak pengamatan dibandingkan dengan kriteria kesesuaian lahan kopi Arabika. Sedangkan untuk melihat hubungan antar karakteristik lahan dan antara karakteristik lahan dengan produksi kopi Arabika Gayo 2 dilakukan analisis korelasi linear berganda. Hasil penelitian menunjukkan bahwa semua satuan lahan pengamatan mempunyai kelas kesesuaian lahan aktual S3 (sesuai marginal) dan S2 (cukup sesuai) dengan faktor pembatas ketinggian tempat, lereng dan sifat kimia tanah. Kelas kesesuaian lahan potensial adalah S2 (cukup sesuai) dengan faktor pembatas ketinggian tempat, lereng, media perakaran (kedalaman efektif), tekstur tanah, batu permukaan serta ketersediaan hara dan S3 (sesuai marginal) dengan faktor pembatas ketinggian tempat. Rata-rata produksi tertinggi diperoleh pada kelas kesesuaian lahan potensial S2 (sesuai) dengan produksi paling tinggi pada ketinggian tempat 1.400 m dpl dan lereng 40 %.